2006
DOI: 10.1051/0004-6361:20053919
|View full text |Cite
|
Sign up to set email alerts
|

Improved low-temperature rate constants for rotational excitation of CO by H$_\mathsf{2}$

Abstract: Cross sections for the rotational (de)excitation of CO by ground state para-and ortho-H 2 are obtained using quantum scattering calculations for collision energies between 1 and 520 cm −1 . A new CO−H 2 potential energy surface is employed and its quality is assessed by comparison with explicitly correlated CCSD(T)-R12 calculations. Rate constants for rotational levels of CO up to 5 and temperatures in the range 5−70 K are deduced. The new potential is found to have a strong influence on the resonance structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 29 publications
11
94
1
Order By: Relevance
“…These include extrapolation to energy levels up to J = 40 and collisional temperatures up to 2000 K, based on the original datasets calculated by Flower (2001) and Wernli et al (2006) for temperatures in the range from 5 to 400 K and energy levels up to J = 29 and J = 20 for collisions with para-H2 and ortho-H2, respectively. We assumed a specific column density N CO Δv −1 ranging from 10 14 to 10 19 cm −2 (km s −1 ) −1 .…”
Section: Lvg Analysismentioning
confidence: 99%
“…These include extrapolation to energy levels up to J = 40 and collisional temperatures up to 2000 K, based on the original datasets calculated by Flower (2001) and Wernli et al (2006) for temperatures in the range from 5 to 400 K and energy levels up to J = 29 and J = 20 for collisions with para-H2 and ortho-H2, respectively. We assumed a specific column density N CO Δv −1 ranging from 10 14 to 10 19 cm −2 (km s −1 ) −1 .…”
Section: Lvg Analysismentioning
confidence: 99%
“…Many experimental and theoretical studies of the collision-inducing rotational energy transfer have been performed in the last four decades. Particularly, the collisional rate coefficients with the most abundant interstellar species, H, H 2 , and He, have been shown to be of great astrophysical importance (Wernli et al 2006;Kłos et al 2007;Guillon et al 2008;Buffa et al 2009;Lique et al 2009Lique et al , 2010Dubernet et al 2009;Najar et al 2009;Sarrasin et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Astronomers usually estimated the rate coefficients for the collisions with para-H 2 ( j = 0) from those obtained by collision with He (Schöier et al 2005). The studies reported by Wernli et al (2006), Lique et al (2008), and Dumouchel et al (2010) indicated that the use of the scaled factor of 1.4 to deduce the rate coefficients of the collision with para-H 2 ( j = 0) from those corresponding to the collision with He provides the correct magnitude order. This was showen to be unlikely for charged species.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that calculations of collisional excitation by ortho-H 2 have been carried out solely on 4 diatomic molecules CO (Flower & Launay 1985;Mengel et al 2001;Flower 2001;Wernli et al 2006), H 2 (Flower & Roueff 1999b), HD (Flower 1999;Flower & Roueff 1999a), SiS (Kłos & Lique 2008, and on water (Phillips et al 1996;Grosjean et al 2003;Faure et al 2007), and that all quantum calculations except those of restricted the H 2 basis set to j 2 = 1.…”
Section: Introductionmentioning
confidence: 99%